Antibacterial Activity of Pomegranate, Orange and Lemon Peel Extracts Against Food-Borne Pathogens and Spoilage Bacteria In vitro and on Poultry Skin - Ramadan , Hazem; Min, Byungjin; Tiwari, Amit K.; Reddy, Gopal; Adesiyun, Abiodun; Jr., Arthur Hinton; Abdela, Woubit (International Journal of Poultry Science, 2015)
This study was conducted to determine the antimicrobial activity of methanol and ethanol extracts of peels of pomegranate (Punica grana), orange (Citrus siensis) and lemon (Limona taris) against four foodborne pathogens (Listeria monocytogenes, Salmonella Typhimurium, Escherichia coli and methicillin-resistant Staphylococcus aureus (MRSA) and a food spoilage bacterium (Pseudomonas fluorescens. Inhibition tests were conducted in vitro using the disc diffusion and minimum inhibition concentration (MIC) assays with the Bioscreen Microbiology analyzer. The study also evaluated the antimicrobial activity of the extracts in situ by determining CFU/ml of bacteria recovered from rinsates of chicken skin treated with the peel extracts and by examining the microflora of treated skin samples using scanning electron microscopy (SEM). The antimicrobial activity of all extracts, except the pomegranate ethanol extract, were dependent on the concentration of extract that the bacteria were exposed to during the trials. Treating the inoculated chicken skin with 5 mg/ml of either the five extracts produced significant (p